Diversity of ambrosia beetles (Coleoptera: Scolytidae) on teak forest in Malang District, East Java, Indonesia - YOGO SETIAWAN; RINA RACHMAWATI; HAGUS TARNO (Biodiversitas Journal of Biological Diversity, 2018)
Setiawan Y, Rachmawati R, Tarno H. 2018. Diversity of ambrosia beetles (Coleoptera: Scolytidae) on teak forest in Malang District, East Java, Indonesia. Biodiversitas 19: 1791-1797. Ambrosia beetle plays an important role in the temperate forest. Ambrosia beetle lives symbiotically with microorganism such as fungi, bacterium, and yeast that can cause plant wilt and death. In Java, ambrosia beetle has been reported to attack teak plantations in some regions. This research aimed to investigate the diversity of ambrosia beetles in the teak plant on monoculture and polyculture system in Malang District. This research was conducted in the teak forest in Dampit and Sumbermanjing Wetan, Malang District from March to May 2017. Ambrosia beetles were trapped by using baited bottle trap with 95% ethanol. The diversity of ambrosia beetles trapped was analyzed using Vegan package in R program to calculate the Shannon-Wiener diversity index (H), Species Evenness index (E), and Simpson's dominance index (D). The results showed that ambrosia beetles trapped in monoculture and polyculture teak plants system consist of nine species, i.e., Xylosandrus crassiusculus, X. morigerus, X. compactus, Xyleborus perforans, Euwallacea simillis, Xyleborinus andrewesi, Premnobius cavipennis, Coccotrypes distinctus, and Hypothenemus hampei. The Shannon Wiener index of Ambrosia beetles in polyculture (H=1.40) was higher than in monoculture (H=1.30), and both locations were categorized in the medium diversity category. The Species Evenness index of ambrosia beetles in polyculture (E=0.67) and monoculture (E=0.66) were also categorized in medium category. The Simpson’s dominance index in both locations was categorized in the middle dominance species. X. crassiusculus was the dominant species in polyculture and monoculture teak plant system.